Free‐living bacterial communities associated with tubeworm (Ridgeia piscesae) aggregations in contrasting diffuse flow hydrothermal vent habitats at the Main Endeavour Field, Juan de Fuca Ridge. Issue 2 (9th February 2013) - Forget, Nathalie L.; Kim Juniper, S.
Abstract: We systematically studied free‐living bacterial diversity within aggregations of the vestimentiferan tubeworm Ridgeia piscesae sampled from two contrasting flow regimes (High Flow and Low Flow) in the Endeavour Hydrothermal Vents Marine Protected Area (MPA) on the Juan de Fuca Ridge (Northeast Pacific). Eight samples of particulate detritus were recovered from paired tubeworm grabs from four vent sites. Most sequences (454 tag and Sanger methods) were affiliated to the Epsilonproteobacteria, and the sulfur‐oxidizing genus Sulfurovum was dominant in all samples. Gammaproteobacteria were also detected, mainly in Low Flow sequence libraries, and were affiliated with known methanotrophs and decomposers. The cooccurrence of sulfur reducers from the Deltaproteobacteria and the Epsilonproteobacteria suggests internal sulfur cycling within these habitats. Other phyla detected included Bacteroidetes, Actinobacteria, Chloroflexi, Firmicutes, Planctomycetes, Verrucomicrobia, and Deinococcus–Thermus . Statistically significant relationships between sequence library composition and habitat type suggest a predictable pattern for High Flow and Low Flow environments. Most sequences significantly more represented in High Flow libraries were related to sulfur and hydrogen oxidizers, while mainly heterotrophic groups were more represented in Low Flow libraries. Differences in temperature, available energy for metabolism, and stability between High Flow and Low Flow habitats potentially explain their distinct bacterial communities. Abstract : This study is the first survey of free‐living microbial diversity associated with the major foundation species at the Endeavour Hydrothermal Vents Marine Protected Area. We combined 454 tag sequencing and Sanger sequencing to characterize the composition and structure of the bacterial communities in contrasting hydrothermal habitats. While the sulphur‐oxidizing genus Sulfurovum was dominant in all samples, we found significant relationships between sequence library composition and habitat type.